Intelligent antithrombotic nanomedicines: Progress, opportunities, and challenges. Issue 2 (12th January 2021) - Xu, Junchao; Zhang, Yinlong; Nie, Guangjun
Abstract: Antithrombotic therapy has long been a trade‐off between antithrombotic effects and hemorrhagic risk. With the aid of nanotechnology, antithrombotic drugs have realized and will further realize highly controllable targeting, disease microenvironment responsive release, imaging‐guided treatment, and reversal agents' development in parallel with novel antithrombotics. Preclinical studies have indicated that intelligent antithrombotic nanomedicines show potential in preventing hemorrhagic risk, evading the balancing act of current antithrombotic treatments. However, none of these nanomedicines have come into clinical trials. In this review, we present a strategic summary of the field of nanoantithrombotics, which is needed to guide the design and application of the next generation of antithrombotic nanomedicines. Herein, we present the recent progress in the preclinical studies of this field, which can be divided into three categories: fibrinolytic, anticoagulant, and antiplatelet therapies. In addition, we provide an outlook on how future antithrombotic nanomedicine design can better overcome the current translational challenges for clinical use. Abstract : Intelligent antithrombotic nanomedicines afford significant improvements in thrombus‐targeting, pharmacokinetics, responsive drug release and reversal agent development, thus decreasing bleeding risk with improved antithrombotic effects.